IMPLEMENTASI KERJASAMA INDONESIA-JERMAN TERKAIT PENINGKATAN KUALITAS PENDIDIKAN SMK DI INDONESIA PERIODE 2017-2019 - Nafa Diantika Destiari (2021)
The high numbers seen by students who graduated from SMK are one of the problems that exist in Indonesia. The government seeks to encourage vocational school graduates to be able to compete in the era of globalization so as to reduce numbers, it is necessary to improve the vocational education system in Indonesia. In this case, Germany plays an important role in being able to bring and help Indonesia to be more advanced in the field of education regarding improving the quality of standardization of vocational education in Indonesia in 2017-2019. The research method used is descriptive qualitative research which is supported by the theory of international cooperation, bilateral cooperation and the concept of sustainable development. The final results of this research will announce and show the efforts made during the cooperation process, so that the final results achieved from bilateral cooperation involving Indonesia- Germany in the field of education produce results with declining numbers and a sophisticated system.